2022
DOI: 10.4103/0972-9062.345180
|View full text |Cite
|
Sign up to set email alerts
|

Changing Paradigm in the epidemiology of Japanese encephalitis in India

Abstract: Japanese encephalitis (JE) is a very serious public health problem in India and the conducive environment permit its emergence in non-endemic areas in the country. There are constant changes taking place in the pattern of current agricultural practices and vector breeding habitats which had far-reaching consequences on the epidemiology of JE and the severity of epidemic outbreaks today. Due to the continuous ecological changes taking place, vectors changed in their breeding dynamics, feeding, and resting behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…These results suggest that the mosquito is likely to be more abundant in urban and peri-urban areas than other Culex spp. It is more attracted to breeding and laying its eggs in polluted water drainage, pits, and stagnant groundwater [5]. It has been reported that mosquitoes are also less frequently found in rural areas [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the mosquito is likely to be more abundant in urban and peri-urban areas than other Culex spp. It is more attracted to breeding and laying its eggs in polluted water drainage, pits, and stagnant groundwater [5]. It has been reported that mosquitoes are also less frequently found in rural areas [9].…”
Section: Discussionmentioning
confidence: 99%
“…Japanese encephalitis (JE) is a zoonotic viral disease that is particularly prevalent in rural areas of Southeast Asia due to the close association of reservoirs and amplifying hosts in pig farms and rice paddy fields [1]. An increase in JE cases in urban and peri-urban areas has recently been reported in Asian countries, including Cambodia [2], Vietnam [3], Lao PDR [4], India [5], and Indonesia [6]. In the Indonesian Province of Bali, human JE cases have been reported to be the highest nationally [6] and occur in rural, urban, and peri-urban areas [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Development of rice paddies combined with free grazing duck farming has also increased the risk of transmission of vector-borne disease like Japanese encephalitis [JE] (Paulraj et al, 2022;Walsh et al, 2022). The rice paddies are vector breeding sites and they also attract wild waterbirds that are natural reservoirs of JE virus and influenza virus.…”
Section: Intensification Of Livestock Farmingmentioning
confidence: 99%